Polymers in aerospace applications - Fried, Joel R. (Rapra review reports, 2008)
This review report gives an overview of how polymers are used in aerospace applications. Topics covered include: Composites, including thermosets, thermoplastics and nanocomposites. Fibre reinforcement of the composites and the specialised applications are also covered. For each type of composite, the chemistry, cure methods, fabrication methods, mechanical properties, thermal properties and environmental degradation are considered. Applications include: sealants, structural adhesives, foams, primer paint, shape memory alloys, electroactive devices, MEMS, vibration damping, NLO properties and.